Language education policy among the Association of Southeast Asian Nations (ASEAN). Issue 1 (April 2017) - Kirkpatrick, Andy
Abstract : This article first traces the development of English in ASEAN to its current role as the sole working language of the organisation and then briefly compares certain of the EU's language polices with ASEAN's. The article points out that English has become the major 'foreign' language taught in ASEAN, often at the expense of local languages. The article argues that, as the major role of English in ASEAN is as a lingua franca, English should be taught as a lingua franca. This would have the added advantage of delaying the teaching of English, thereby allowing primary schools to focus more on local languages. The article concludes with a case study of Myanmar, for which a language education policy is suggested.